The efficiency of AFLP and SSR markers in genetic diversity estimation and gene pool classification of common bean (Phaseolus vulgaris L.) - Marko MARAS; Jelka ŠUŠTAR-VOZLIČ; Branka JAVORNIK; Vladimir MEGLIČ (Acta Agriculturae Slovenica)
The present work was conducted to evaluate AFLP (Amplified Fragment Length Polymorphism) and SSR (Simple Sequence Repeat) marker systems for their ability to detect genetic diversity within a set of 29 common bean accessions spanning both the Andean and Mesoamerican gene pools and to compare the efficiency of these two marker types in the classification of accessions according to the gene pools of origin. The ten AFLP primer combinations produced 112 polymorphic bands, while 14 SSR primer pairs generated 100 polymorphic bands. Almost two-fold higher value of expected heterozygosity was calculated for SSR (0.63) than for AFLP (0.32). As the result of a higher multiplex ratio component (11.20), higher marker index value was observed for AFLP (3.56) in comparison to SSR (0.63). The higher level of polymorphism detected by SSR markers has contributed to the lower genetic similarity estimates based on SSR markers (mean 0.25) as compared to AFLP markers (mean 0.88). The dendrograms generated with hierarchical UPGMA (Unweighted Pair Group Method with Arithmetic mean) cluster analysis of the Jaccard's similarity coefficient matrices revealed two major clusters, which were identified as the Andean and the Mesoamerican gene pools. Both marker systems showed comparable accuracy in grouping genotypes of common bean according to their gene pool of origin.